Effect of masking and fatigue on acoustic reflex threshold (ART) - Vyasamurthy MN; Satyan HS (Journal of All India Institute of Speech and Hearing, 1970)
Masking and fatigue are two different processes (Ward 1963). Masking represents the change of threshold for one auditory stimulus concurrently with the presentation of a second stimulus. For example, a subject has a threshold of lOdB at 4 KHz, in the presence of a broad-band noise at 80dB SPL his threshold of hearing at 4 KHz may increase to 50dB HL. Here, the difference in the thresholds at 4 KHz (40 dB) is referred to as the threshold shift brought about by the masking noise. The threshold in the presence of the noise is referred toas masked threshold. Masking is regarded as a ' line-busy' phenomenon and as such there is a great deal of neural activity